Nietzsche's Hyperanthropos-Centrism - Causey, Robert Mark (The Trumpeter, 2014)
In this article I examine Nietzsche's compatibility with Deep Ecology. I examine some important arguments for and against reading Nietzsche as an environmental philosopher. By introducing Arne Naess and Deep Ecology into the discussion, I show that Nietzsche can be effectively read as a forerunner to Deep Ecology, especially with his concept of the Ubermensch which he envisions as the human reintegrated into nature.